2021
DOI: 10.3390/nu13020652
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nutraceuticals Mixture Improves Liver Steatosis by Preventing Oxidative Stress and Mitochondrial Dysfunction in a NAFLD Model

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the leading cause of liver disease globally, and represents a health care burden as treatment options are very scarce. The reason behind the NAFLD progression to non-alcoholic steatohepatitis (NASH) is not completely understood. Recently, the deficiency of micronutrients (e.g., vitamins, minerals, and other elements) has been suggested as crucial in NAFLD progression, such that recent studies reported the potential hepatic antioxidant properties of micronutrients su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In the present study, all tested diets led to a decrease in SOD2 and PrxIII amounts, which was significant in the HF-F group and was not prevented in the HF-F-D rats, thus demonstrating the mitochondrial oxidative stress induced by all diets. These findings agree with other reports showing marked oxidative stress inside mitochondria because of the obesogenic diets administered [ 23 , 31 ]. In particular, in liver from genetically modified mice, placed on an obesogenic diet, the diminished expression and activity of SOD2 have been described [ 32 ].The reduction of the mitochondrial scavenger protein PrxIII has been reported in various conditions featuring oxidative stress inside the organelles [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, all tested diets led to a decrease in SOD2 and PrxIII amounts, which was significant in the HF-F group and was not prevented in the HF-F-D rats, thus demonstrating the mitochondrial oxidative stress induced by all diets. These findings agree with other reports showing marked oxidative stress inside mitochondria because of the obesogenic diets administered [ 23 , 31 ]. In particular, in liver from genetically modified mice, placed on an obesogenic diet, the diminished expression and activity of SOD2 have been described [ 32 ].The reduction of the mitochondrial scavenger protein PrxIII has been reported in various conditions featuring oxidative stress inside the organelles [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other extra FFAs derive from hepatic “de novo” lipogenesis, through which the surplus dietary energy, mostly introduced as carbohydrates and fat, is partially used, leading to the massive deposition of triglycerides and resulting steatosis [ 30 ]. The imbalance of ETC activity in NAFLD models and patients has been largely described in the literature and thoroughly examined [ 31 ]. In the latter study, the activities of ETC complexes were analyzed and found to decrease for all complexes but Complex II in the NAFLD model.…”
Section: Discussionmentioning
confidence: 99%
“…The lock micronutrients have been reported as crucial in NAFLD progression [147]. Sangineto et al [148] explored the probable beneficial effects of dietary supplementation with FLINAX, an innovative composition of nutraceuticals (vitamin E, vitamin D3, olive dry-extract, cinnamon dry-extract and fish oil) in a NAFLD model characterized by oxidative stress and mitochondrial function damaged. The Flinax group significantly presented lower hepatic fat accumulation compared to non-supplemented.…”
Section: Other Therapeutic Approachesmentioning
confidence: 99%
“…Reduced: serum ceramide content reduced, (p < 0.05), hepatic triglyceride, ALT, AST, hepatic inflammation, amount of inflammatory cell; Bcl-2 expression restored, (p < 0.05); 2019 [87] Fenretinide Mice Lowered: plaque area 50.8% (p < 0.05), plasma lipid levels by 20.1%, (p < 0.05), and plasma ceramides; 2020 [156] Diet Mice Flinax reduced lipoperoxidation markers, hepatic fat accumulation restores complex I, III, V (ATP-synthase), lower peroxides levels, (p < 0.05), no difference in complex IV, and higher production of CPT1A and CPT2; 2021 [148] Alphamangostin Mice Inhibits: ceramide content, and, Inhibites aSMase activity, 2021 [146] Farnesoid X receptor Mice Lower: ceramide content, hepatic cholesterol levels, mRNA levels of Smpd3 elevates hepatic Cyp7a1 mRNA levels Repressed lesion areas in aortas and smaller atherosclerotic lesions; 2021 [120] Liraglutide Mice Gene expression Sptlc2, cerS4, and cerS6 decreased; C16 and C24 accumulation was limited (p < 0.05); Unchanged: saturated fatty acid, phospholipids with long chains-reduced, phospholipids with very long chains 2021 [132]…”
Section: Degs1 Gene Micementioning
confidence: 99%
“…Recently, various nutraceuticals with lipid-lowering effects have attracted much attention [ 18 , 19 ], including citrus-derivatives such as citrus peel extracts, citrus flavonoids, and citrus polymethoxyflavones [ 20 ]. Furthermore, epidemiological studies have demonstrated that the intake of citrus flavonoid-containing foods is associated with a decreased incidence of CVD [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%